O processo de institucionalização da educação a distância na Universidade Federal de São Carlos (UFSCar) no período de 2004 a 2018 - Chaquime, Luciane Penteado (2019)
The institutionalization of distance education (DE), based on the Institutional Theory, can be understood as a process based on the dynamics of interaction between the university and the educational field. His analysis then includes, on the one hand, exogenous elements related to the pressures exerted by the field for the university to offer courses at a distance. On the other hand, it involves endogenous elements related to the continuous and gradual adaptations carried out by the university to systematically insert the DE into its internal structural arrangement in order to legitimize itself socially. In Brazil, DE settled in the educational field with Law 9.394/1996, being configured as a modality with the potential to democratize the access to Higher Education. The Universidade Aberta do Brasil System (UAB), instituted in 2006, consisted of the most relevant public policy in the induction of distance courses offered by public higher education institutions that, from the moment of adhesion, initiate the necessary structural and organizational changes and changes to meet the specificities concerning the management of DE systems. Therefore, the general objective of this thesis was to analyze the institutionalization of the DE at the Federal University of São Carlos (UFSCar) and the specific ones were: to identify and describe the history of the institutionalization of DE in UFSCar, relating it to the educational field Brazilian; characterize the structure of academic-pedagogical and administrative management created to support the offer of courses in the distance modality, as well as the type of DE adopted by UFSCar; mapping and analyzing the factors that limit the institutionalization of DE in the university, identifying its nature; identify and analyze the most significant elements in favor of the institutionalization of DE in UFSCar and; to analyze the perspectives regarding the institutionalization of DE at UFSCar. In order to do so, a qualitative research was carried out, through the survey and study of bibliography, data collection through documental research techniques and semi-structured interviews, data analysis and dissemination of results. Among the main results, the following stand out: the beginning of the institutionalization of the DE in UFSCar is related to the adhesion to the UAB System for the offer of five undergraduate courses, which led to the creation of an DE unit that was incorporated into the structure of the university, as well as rules, procedures and regulations regarding the modality; the institutionalization of the modality in UFSCar represented the conciliation between its social function of democratizing access to higher education and its maintenance as an organization that aims to survive in the field in which it operates; the trends for the continuity of the institutionalization at UFSCar point to the encouragement of Blended Learning and also suggest a greater submission of the university to the market as the offer of specialization courses is increased, and partnerships are sought with the private sector as a way of maintaining the activities of the unit manager of DE in UFSCar.